2015
DOI: 10.1186/s12889-015-1938-4
|View full text |Cite|
|
Sign up to set email alerts
|

Clustering of non-communicable diseases risk factors in Bangladeshi adults: An analysis of STEPS survey 2013

Abstract: BackgroundNon-communicable diseases (NCDs) have already become major killers in Bangladesh. Once NCDs are developed, they become chronic health and economic problems. Their primary prevention is linked to their common risk factors. This study was conducted to determine the prevalence of NCD risk factors with a focus on their clustering in Bangladeshi adults.MethodsThis nationally representative study was done in 4,073 (1,812 men and 2,261 women) adults aged 25 years or older selected from rural and urban house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
108
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(137 citation statements)
references
References 19 publications
9
108
6
Order By: Relevance
“…This might have favored easy availability and use of smokeless tobacco products such as Zarda, Pan Masala, Gul, etc. 17 We found low per capita consumption of fruit/ vegetable per day in our study which is similar that of STEPS surveys done in 2010 7 and 2013. 8 Low consumption of fruits and vegetables probably could be due to the lack of awareness, especially in rural area.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This might have favored easy availability and use of smokeless tobacco products such as Zarda, Pan Masala, Gul, etc. 17 We found low per capita consumption of fruit/ vegetable per day in our study which is similar that of STEPS surveys done in 2010 7 and 2013. 8 Low consumption of fruits and vegetables probably could be due to the lack of awareness, especially in rural area.…”
Section: Discussionsupporting
confidence: 85%
“…The overall prevalence of smoking (31.0%) observed in the present study is quite high than STEPS survey 2010 (27%) 7 and STEPS survey 2013(17%) 8 done in Bangladesh. Smoking prevalence among men in the present study (58.4 %.)…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The difference could be attributed to study populations, with this study exploring the perceptions of healthcare providers' nationwide, while the previous studies were on members of the public living in specific locations. The results of this study showed a 79.8% perceived prevalence of unhealthy diet, which is lower than the 93% reported in Bangladesh (Zaman et al, 2015). The difference might be attributed to geographical location, cultural norms and food habits.…”
Section: Discussioncontrasting
confidence: 52%
“…2 Both NCDs and their risk factors are showing an increasing trend. 3,4 These risk factors are tobacco use, low intake of fruits and vegetables, physical inactivity, obesity, excessive alcohol consumption, raised blood pressure, and raised blood glucose and cholesterol. 5 Evidences show that the detection and treatment rate of diabetes mellitus and hypertension is also inadequate among Bangladeshi population.…”
mentioning
confidence: 99%